Avaliação dos registros de enfermeiros no cuidado à pessoa com tuberculose na atenção primária - Silva Júnior, José Nildo de Barros (2021)
Introduction: The nurse's record in the user's medical record is an important tool in supporting the health care process, a source of clinical and administrative data that assists in decision making, a form of shared communication between all health professionals, a legal record of the care implemented, and a support for research. Therefore, it is vital to evaluate the quality of nurses' records in the care of patients with tuberculosis in Primary Health Care, as this will contribute to the production of health indicators in order to achieve the goals proposed by the World Health Organization in the search for the eradication of the disease. Objective: To evaluate the quality of records of nurses in the care of people with tuberculosis monitored in Primary Health Care. Method: A documental study of quantitative design, developed in the Family Health Units, belonging to the Sanitary Districts, in the municipality of João Pessoa- PB. Data collection occurred in the period from August to October 2020 in 190 medical records, selected through a probabilistic technique of systematic sampling, using a structured form. The data collected were analyzed using the software R version 4.0.3, assuming a significance level of 5%. Descriptive statistics were used, using the Pareto diagram and trend analysis. The project was approved under opinion number 4.003.210, with CAAE 30324820.6.0000.5188. Results: As the main indicators with the highest percentage of non-completeness, demographic characteristics (94.7%), prejudice (91.1%), diagnostic nursing process (88.9%) and propaedeutic findings (85.2%) stood out, these total 25% of the overall incompleteness evidenced by the Pareto Diagram. The indicators that showed significant increasing trend were: style and life conditions (p=0.0088), physical examination (p=0.0352), consultation orientations (p=0.0161) and presentation (p=0.0009), while the indicator that showed decreasing trend of non-completeness was the indicator prejudice (p=0.0077). Conclusion: The findings showed unsatisfactory completeness of the record of nurses in the medical record against TB in PHC, enabling reflection regarding the importance of carrying out the nurse's record, emphasizing the need for care to be documented, be adequate, reliable, consistent and complete, in view of the quality, uniqueness and continuity of care, production of indicators for decision making, legal evidence and audit, quality assurance of records, permanent report, teaching and research.